An analytical study on the witness protection act 2009 / Norhafiza Ali...[et al.] - Ali, Norhafiza; Hassim, Syairah; Sape'i, Khairul Anis Shafikah; Wan Muhamad Saridan, Wan Hafsah (2010)
The issue of witness intimidation has been brought up by many countries many years ago. This problem triggered come countries to come up with a legislative approach to protecting the witnesses through the enacting of a specific witness protection statute. This statute, though labelled with a variety of names, is basically established with one common objective, which is to provide protection and assistance to witnesses, especially for important witnesses who will testify in court. Witness protection assistance is important to help protect the witness from any threats which might be made by persons whom the witness might testify against. Threat or intimidation to the witness can take place in many ways. Therefore, any protection assistance should be able to overcome each and every threat so as to effectively shield the witness from these intimidations. The introduction of the Witness Protection Act in Malaysia could be regarded as one approach adopted by the government to overcome the above problem. This Act has been gazetted in the year of 2009. However, the existence of it has not been largely discussed by the media. The same goes to its implementation. This could be because the Act has just been 'newly-born' and there is still not much application to date. The Witness Protection Act 2009 is one of the government's missions in providing a transparent and effective legal justice, especially in cases brought before the court. However, as there have been many issues of corruption and political influence in the judicial branch in the country, it is arguable that the Act enacted might not withstand this challenge in order to serve its objectives efficiently. This study will basically include the discussion on the above issues and also other related issues on the readiness of the Act to serve its main purpose in protecting witnesses especially in the current situation in Malaysia. This paper will also examine the adequacy of protection given by the Act as well as consider how the present provisions could be improved upon. It is hoped that by conducting this research, we can bring about a better and more effective witness protection system.